PENGUJIAN DNS HEALTH DENGAN DNS BENCHMARK - Eka Firdaus; Rizal Munadi; Teuku Yuliar Arif (J-Innovation, 2016)
The concept of Domain Name System (DNS) health is a way to determine whether the DNS is working right, by taking examples like the health of human body. Bad quality of the university DNS server can affect the performance of the university's website that can be accessed proper by users. To evaluate the DNS performances, experimental method is conducted to find and measure response time and reliability. This parameters are analyzed to show DNS health using DNS Benchmark tool. This test involved 34 university’s websites that spread in Indonesia and has been done for two weeks. The results has shown that there are 34 university’s DNS server in a good condition.